2017
DOI: 10.3390/toxins9050150
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Indole Alkaloid 3α-Acetonyltabersonine Induces Glioblastoma Apoptosis via Inhibition of DNA Damage Repair

Abstract: Cytotoxic indole alkaloids from Melodinus suaveolens, which belongs to the toxic plant family Apocynaceae, demonstrated impressive antitumor activities in many tumor types, but less application in glioblastoma, which is the lethal brain tumor. In the present study, we reported the anti-glioblastoma activity of an indole alkaloid, 3α-acetonyltabersonine, which was isolated from Melodinus suaveolens. 3α-acetonyltabersonine was cytotoxic to glioblastoma cell lines (U87 and T98G) and stem cells at low concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Moreover, 3α-acetonyltabersonine was shown to inhibit the DNA damage repair process and induce apoptosis through the activation of MAPK phosphorylation (p-ERK and p-JNK). And the in vivo experiment showed that 3α-acetonyltabersonine could prolong the survival time of the glioblastoma mouse model [ 140 ]. Additionally, a β-carboline alkaloid, flavopereirine, was also found to trigger cell cycle arrest, suppress the activation of AKT, and increase the ERK and p38 MAPK expression level, ultimately resulting in the induction of apoptosis in MDA-MB-231 cells [ 141 ].…”
Section: Targeting Apoptotic Signaling Pathways With Indole Alkaloids...mentioning
confidence: 99%
“…Moreover, 3α-acetonyltabersonine was shown to inhibit the DNA damage repair process and induce apoptosis through the activation of MAPK phosphorylation (p-ERK and p-JNK). And the in vivo experiment showed that 3α-acetonyltabersonine could prolong the survival time of the glioblastoma mouse model [ 140 ]. Additionally, a β-carboline alkaloid, flavopereirine, was also found to trigger cell cycle arrest, suppress the activation of AKT, and increase the ERK and p38 MAPK expression level, ultimately resulting in the induction of apoptosis in MDA-MB-231 cells [ 141 ].…”
Section: Targeting Apoptotic Signaling Pathways With Indole Alkaloids...mentioning
confidence: 99%
“…[56][57][58][59][60] Research shows the cytotoxic effect of tabersonin against various cancer cell cultures. [61][62][63] Terpenoids are other secondary metabolites identified in the purnajiwa sample. The terpenoids identified in the Jimbaran fruits sample is aristolin, while 64 Fatty acids are another class of compounds identified in purnajiwa samples.…”
Section: Resultsmentioning
confidence: 99%
“…The 3 -acetonyltabersonine was the agent that impeded the repair of DNA damage mechanisms. It is of crucial importance and enhances the anticancer mechanism in indole alkaloids to have 3α-acetonyltabersonine, which prevents DNA damage repair and the buildup of DNA damage that impacts the genome integrity [70].…”
Section: α-Acetonyltabersoninementioning
confidence: 99%